Spontaneous Poisoning by Blutaparon portulacoides in a Horse - Pedroza, Heloísa de Paula; Pinho Neto, Antônio Catunda; Melo, Marília Martins; Soto-Blanco, Benito (Acta Scientiae Veterinariae, 2019)
Background: In the Rio Grande do Norte state, Northeastern Brazil, several outbreaks of poisoning affecting horses, cattle and sheep have been attributed by a number farmers to the consumption of the leaves of Blutaparon portulacoides, a plant from family Amaranthaceae, known as “pirrixiu”, “bredo-de-praia” and “capotiraguá”. However, the spontaneous poisoning was reported in the literature exclusively in sheep. Thus, the present study aims to report the clinical signs found in a spontaneous poisoning by B. portulacoides in a horse. Case: A 8-year-old mixed-breed mare, weighing 268 kg, was referred to veterinary care showing loss of appetite and diarrhea. The clinical evolution was reported by the owner as for six days. During the physical examination, the animal presented slight apathy, pale mucous membranes, tachypnea, dehydration, intestinal hypermobility, and watery diarrhea. The predominant plant in the paddock where the mare was maintained was B. portulacoides. According to the owner, the poisoning by this plant is common in the neighborhood of the farm and has already occurred in other species (cattle and sheep). After the origin of poisoning was identified, the access to the plant was restricted and it was established fluid therapy to treat the dehydration. After three days, the animal returned to eat normally and the diarrhea ceased. Discussion: The exclusive feeding of sheep with B. portulacoides is responsible for disorders in the digestive tract, characterized by softening of feces and intestinal epithelial lesions (intestinal villi epithelium detachment, goblet cell hyperplasia, submucosal inflammatory cells infiltrate and infiltration of the lamina propria by mononuclear cells). Given the similarity of the frame displayed by the horse, described in the present report, it is believed that the sensitivity to poisoning by B. portulacoides is not exclusive to sheep, but also occurs in horses. Taking into account that B. portulacoides is found widespread through the Atlantic coast of Brazil, it is feasible to speculate that several other cases of poisoning might occur without accurate diagnosis. A plant that promotes similar poisoning is Portulaca elatior Mart. (family Portulacaceae), described in the literature affecting goats, sheep, and cattle. However, the poisoning by P. elatior is typically acute, showing clinical evolution within 48 hours after ingestion of the plant, whereas B. portulacoides poisoning occurs after a few days of consumption. Phytochemical analysis of B. portulacoides leaves revealed the occurrence of a number compounds, including three steroids, one flavone, one isoflavone and two flavonoids. However, the toxic principle of the plant is still unknown. The possible mechanism of poisoning is the osmotic imbalance in the digestive tract promoted by scarcity of sodium and excess of magnesium, potassium and calcium in the plant. Future studies are desirable to determine the toxic principle present in B. portulacoides and the exact mechanism of poisoning. In conclusion, the clinical presentation of the referred mare is similar to that described in sheep that ingested Blutaparon portulacoides, thus this plant can be considered as responsible for toxic effects in the digestive system of horses.